2022
DOI: 10.1002/dvdy.450
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐injury procedure‐induced cardiac regeneration shows unique gene expression profiles in the newt Pleurodeles waltl

Abstract: Background Cardiac regeneration in the adult mouse is not substantial. Some vertebrates, such as newts and zebrafish, regenerate the heart throughout their lives. To understand how regenerative abilities differ among animal species, comparative research has been conducted in animals like mouse, zebrafish, and newt. For those purposes, cryo‐injury is suitable as an experimental model for the pathological condition of human myocardial infarction. In fact, cryo‐injury procedures are common in mouse and zebrafish.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…In the Iberian ribbed newt (Pleurodeles waltl), conflicting reports exist as to whether the post-metamorphic heart regenerates efficiently following cryoinjury. In one study, cardiac scarring that gradually reduced in extent, but persisted for at least 10 months after injury, was described, indicating the absence of an efficient regenerative response 36 . A second study, however, demonstrated complete resolution of cardiac fibrotic tissue within 210 days of cardiac injury 37 .…”
Section: [H2] Fish and Amphibiansmentioning
confidence: 99%
“…In the Iberian ribbed newt (Pleurodeles waltl), conflicting reports exist as to whether the post-metamorphic heart regenerates efficiently following cryoinjury. In one study, cardiac scarring that gradually reduced in extent, but persisted for at least 10 months after injury, was described, indicating the absence of an efficient regenerative response 36 . A second study, however, demonstrated complete resolution of cardiac fibrotic tissue within 210 days of cardiac injury 37 .…”
Section: [H2] Fish and Amphibiansmentioning
confidence: 99%
“…To facilitate such cross‐species comparisons, the method of inducing regeneration (by inducing injury) should be similar. In fact, it has been reported that the gene expression profiles during the process of cardiac regeneration differ between the amputation method and the cryo‐injury method (Simões et al, 2020; Uemasu et al, 2022). Known techniques of inducing injury in myocardial tissue include amputation (resection), cryo‐injury, and coronary artery ligation.…”
Section: Background and Featuresmentioning
confidence: 99%
“…On the other hand, no cryo‐injury model had been established for newts. Recently, however, several groups have reported cryo‐injury models of heart regeneration in the Iberian ribbed newt and in axolotl, a species that is closely related to newts (Dittrich et al, 2018; Dittrich & Lauridsen, 2021; Eroglu et al, 2022; Uemasu et al, 2022). The Iberian ribbed newt, Pleurodeles waltl , has been used as useful model animal in recent years (Elewa et al, 2017; Hayashi et al, 2013; Hayashi et al, 2014; Hayashi et al, 2019; Kyakuno et al, 2021; Matsunami et al, 2019; Suzuki et al, 2018).…”
Section: Background and Featuresmentioning
confidence: 99%
“…Further reconstructions from different angles and volume‐rendered images can be achieved through post‐analysis using image processing software. This technique preferentially visualizes mineralized bone when unstained (Slater et al, 2009), whereas soft tissues can be stained with iodine and heavy metal compounds (Degenhardt et al, 2010; Gignac et al, 2016; Lesciotto et al, 2020; Metscher, 2009a; Uemasu et al, 2022; Weinhardt et al, 2018). Owing to its capability to perform advanced three‐dimensional (3D) morphological analysis, this technique has recently been applied in the field of developmental biology (Hsu et al, 2016; Metscher, 2009b; Schoborg et al, 2019; Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%